The effects of zingerone on differentiation and signalling pathways in bone cell lines and bone health parameters in Sprague Dawley rats - Nyakudya, Trevor Tapiwa (University of Pretoria, 2025)
Thesis (PhD (Human Physiology))--University of Pretoria, 2025.